E-GOVERNANCE AS AN ELEMENT OF E-DEMOCRACY IN UKRAINE - Сопілко, Ірина Миколаївна; Сай, Регіна Євгеніївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article is devoted to the process of implementing the concept of e-governance as an important element of e-democracy in Ukraine. Today’s major innovations in the world are related to the use of information technologies, including such innovative achievements being actively applied by public authorities in different countries. Speaking about technological advances, it should be noted that they empower public authorities to bring their decisions to the attention of citizens quickly, and citizens are given the opportunity to be heard in response. In particular, it provides opportunities for indifferent citizens to be informed about urgent problems in the state, as well as to monitor the activities of state and local self-government bodies. In addition, citizens are given the right to offer other ways to solve certain problems, to receive quality services. Research methods: the research was carried out using generally accepted methods of scientific knowledge, such as analytical, comparative legal, semantic-cognitive, system, statistical, and others. The basis of the methodology in this study is a systematic approach by which a certain object is considered as a multidimensional phenomenon consisting of various elements, the relationship between which is formed by a relatively stable structure, as a result forms a new institution. Results: the approach to understanding the concepts of «e-governance» and «e-democracy» is defined. The problems of introduction of new technologies in Ukraine and prospects for its development are revealed. Discussion: search for ways to improve legislation in the field of digital transformation and development of the information society. We analyzed the main approaches to understanding the concepts of «e-government» and «e-democracy», as well as ways to implement them in Ukraine. The above concepts are considered only as convenient technologies for the transition to the information society, the approach in which they are considered as the latest form of government, which is a necessary part of the large-scale transformation of society into a New Age society. The main elements of interaction in the information society are: the state and the citizen, the state and business, and government. We also proposed our own definitions of these concepts, taking into account the peculiarities of the current state and trends in the information society.